2006
DOI: 10.1590/s1517-83822006000100004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bacterial plaque suppression and recolonization by S. mutans and S. sobrinus

Abstract: The in vitro study of the interactions between S. mutans and S. sobrinus is important to determine the role of these microorganisms in the formation of biofilms on dental structures and their potential to induce carious lesions. The objective of this research was to study the suppression of bacterial plaque formation and its recolonization by rifampycin-resistant S.mutans and streptomycin-resistant S. sobrinus. To study the competitive relationship between these species, previously standardized strains were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The association between the species S. mutans and S. sobrinus appears to favor an increase in caries index of individuals. The occurrence of the species S. mutans in 69.0% of the individuals in this study can be related to their capacity to inhibit the formation of bacterial biofilm by other species and recolonize the tooth surface as shown in a study by Pereira et al [27]. The results obtained in the present study regarding the identification of S. mutans and S. sobrinus coincided with those of cited studies and show that these species had a high prevalence in the specimens isolated as well as in the individuals studied.…”
Section: Discussionsupporting
confidence: 54%
“…The association between the species S. mutans and S. sobrinus appears to favor an increase in caries index of individuals. The occurrence of the species S. mutans in 69.0% of the individuals in this study can be related to their capacity to inhibit the formation of bacterial biofilm by other species and recolonize the tooth surface as shown in a study by Pereira et al [27]. The results obtained in the present study regarding the identification of S. mutans and S. sobrinus coincided with those of cited studies and show that these species had a high prevalence in the specimens isolated as well as in the individuals studied.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, S. mutans colocalized with S. sobrinus in the biofilm ( Fig. 4 A), which indicated that the two species might have a symbiotic relationship and accelerate the progression of caries when combined [ 42 , 43 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Streptococcus mutans is closely associated with dental caries, mainly those involving smooth surfaces [2]. The primary habitats for S. mutans are mouth, pharynx and intestine.…”
Section: Introductionmentioning
confidence: 99%